Student housing a resilient housing rental market: case of federal polytechnic neighbourhood Bauchi, Nigeria - Ghani, Zubairu Abubakar; Sulaiman, Noralfishah; Mohammed, Mohammed Ishaq (Path of Science, 2018)
In the last three decades globally higher institutions (HIs) have been experiencing an unprecedented upsurge in student population and student enrolment in His generally outstrip the HIs student housing. In many countries of the world like Nigeria, HIs are obviously incapacitated in accommodating the growing student population which compelled numerous students to overflow into their HIs’ neighbourhood seeking for alternative housing accommodation in the private housing rental market. Indeed the scenario of HIs student's housing shortfalls and increasing students housing demand evolved the interest of many people in a student housing rental market. This is because it has been uncovered that business in student housing rental is lucrative and guaranteeing business that ensured profit for a long term. This paper, therefore, explores the nature and landscape of student housing rental in Nigeria where the business is immature then drawn the conclusion.